2000
DOI: 10.1136/ard.59.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of development and joint pathology on stromelysin enzyme activity in equine synovial fluid

Abstract: Objective-To investigate the role of stromelysin (MMP-3) activity in synovial fluid (SF) at diVerent stages of development and in common joint disorders in the horse. Methods-Stromelysin activity was determined with a fluorogenic enzyme activity assay in SF of normal joints of fetal, juvenile and adult horses, and in SF of horses suVering from the developmental orthopaedic disease osteochondrosis (OC) or osteoarthritis (OA). Additionally, MMP-3 activity was expressed as a ratio of previously reported general M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 13 publications
2
35
1
Order By: Relevance
“…Several Wnt proteins, including Wnt-1, are required for skeletal tissue morphogenesis during development (15,17,46). Fibronectin and several MMPs, including MMP-3, are essential mediators of these developmental processes (47)(48)(49). Although the effects of Wnt signaling on fibronectin and MMP-3 expression during developmental processes have not been studied in great detail, our experiments suggest that Wnt-1-like signals in mesenchymal fibroblasts may influence both fibronectin and MMP-3 expression in the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…Several Wnt proteins, including Wnt-1, are required for skeletal tissue morphogenesis during development (15,17,46). Fibronectin and several MMPs, including MMP-3, are essential mediators of these developmental processes (47)(48)(49). Although the effects of Wnt signaling on fibronectin and MMP-3 expression during developmental processes have not been studied in great detail, our experiments suggest that Wnt-1-like signals in mesenchymal fibroblasts may influence both fibronectin and MMP-3 expression in the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…Working on experimentally induced TMJ OA in sheep, Miyamoto et al (2002) demonstrated that activated MMP-2 levels correlated with the initial articular cartilage destruction (2-4 weeks) rather than with the progression of OA while pro-MMP-2 was detected in all age groups. Most of the research on the involvement of MMPs in aging and OA in animals was performed on knee joint cartilages (Brama et al 1998(Brama et al , 2000Flannelly et al 2002;Price et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Upon cleavage, quenching is lost, and an increase in fluorescence is measured proportional to the amount of hydrolysed substrate (Beekman et al, , 1999. We have designed fluorogenic substrates using fluoresceinyDabcyl as the fluorophoreyquencher combination (Beekman et al, 1999); these substrates are approximately 100-200 times more sensitive than previously used substrates in which EDANSyDabcyl acted as the fluorophorey quencher combination (Beekman et al, , 1999Brama et al, 1998Brama et al, , 2000. We have developed formats in which it is possible to determine MMP-1 (collagenase 1) activity, MMP-3 (stromelysin 1) activity or gelatinolytic (MMP-2, MMP-9 and MMP-13) activity.…”
Section: Introductionmentioning
confidence: 99%